2021
DOI: 10.1111/mec.16319
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost thaw with warming reduces microbial metabolic capacities in subsurface soils

Abstract: Microorganisms are major constituents of the total biomass in permafrost regions, whose underlain soils are frozen for at least two consecutive years. To understand potential microbial responses to climate change, here we examined microbial community compositions and functional capacities across four soil depths in an Alaska tundra site. We showed that a 5-year warming treatment increased soil thaw depth by 25.7% (p = .011) within the deep organic layer (15-25 cm). Concurrently, warming reduced 37% of bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 82 publications
4
9
0
Order By: Relevance
“…Our NCM and NST analyses indicated that passive dispersal and ecological drift may contribute more to community assembly of bacteria than fungi, possibly due to their contrasting body sizes (Luan et al, 2020). The trend for bacterial community assembly under warming was progressively dominated by deterministic factors in the dry season, similar to previous studies in high‐latitude tundra and grassland (Feng et al, 2020; Guo et al, 2018; Wu et al, 2022), suggests that temperature may be a major driver in ecosystem (Zhou et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Our NCM and NST analyses indicated that passive dispersal and ecological drift may contribute more to community assembly of bacteria than fungi, possibly due to their contrasting body sizes (Luan et al, 2020). The trend for bacterial community assembly under warming was progressively dominated by deterministic factors in the dry season, similar to previous studies in high‐latitude tundra and grassland (Feng et al, 2020; Guo et al, 2018; Wu et al, 2022), suggests that temperature may be a major driver in ecosystem (Zhou et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…2B ), filling major knowledge gaps in the understanding of the linkage between viruses and edaphic conditions ( 44 ). Markedly, soil depth, rather than warming treatment, was a strong factor in determining viral community and functional gene structures, which was consistent with previous study of bacterial communities in this region ( 23 ). The beta diversity, the abundance patterns of vOTUs, and the similarity clustering network based on viral shared protein clusters revealed that viral community composition was highly endemic by soil depth.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, warming significantly decreased (Student t test, P < 0.05) the stochastic ratio of viral communities at 45 to 55 cm ( Fig. 2C ), suggesting that warming could impose deterministic effects on viruses ( 23 ). For viral function, stochastic ratios were consistently <50%, indicating that viral functional traits were highly deterministic ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated that bacteria in permafrost peatlands were adapted to a low temperature and N-limited environment. In line with our results, warming reduced 37% of bacterial abundance and microbial metabolic capacity in the deep organic layer of an Alaska tundra ( Wu et al, 2022 ). Our results showed that the combined effects of temperature rising and N addition significantly increased fungal abundances and there were significantly positively correlations between fungal abundances and the emissions of CO 2 and N 2 O, suggesting that there were differences in sensitivity of different microbial communities to environmental changes and fungi communities played a vital part in the variations of CO 2 and N 2 O emissions at higher temperature and under the addition of N. Consistent with the outcomes of the current study, Xu et al (2017) determined that fungal tolerance to high temperatures played a significant part in N 2 O emissions.…”
Section: Discussionsupporting
confidence: 90%